Role of oral clonidine on intraopereative haemodynamic stability for craniotomies of intracranial space occupying lesion - Selina, F; Akhtaruzzaman, KM; Talha, KA; Hossain, MM; Iqbal, KM (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 257-263 The abstract of this article is available on the PubMed website